Text and image digitisation - a general overview of terminology and technology of digitisation - Badurina, Boris (Array, 2000)
Text and image digitisation - general overview of terminology and technology of digitisation ; practical part: scanning, OCR, text editing, image digitising, creation of .pdf or .html digitised document, search engine implementation ; discussion of problems concernig digitisation.